PENYULUHAN KELUARGA BERENCANA ( KB) PADA DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP3P2&KB) KOTA PADANG - Rini Parmila Yanti; Zulkarnaen Zulkarnaen (Jurnal Public Administration, Business and Rural Development Planning, 2019)
From the objectives of the research carried out, namely: 1. To find out family planning counseling at the Office of Women's Empowerment of Child Protection for Population Control and Family Planning (DP3AP2 & KB) Kota Padang 2. To find out the factors that influence the implementation of counseling. Family Planning By the Office of Women's Empowerment of Child Protection Population Control and Family Planning (DP3AP2 & KB) Padang City. This study uses descriptive method with a qualitative approach. From the results of the research and discussion, the following conclusions and suggestions were obtained: 1. Family planning counseling at the Office of Women's Empowerment of Padang Population Control and Family Planning (DP3AP2 & KB)